Comparative effectiveness of teriflunomide vs dimethyl fumarate in multiple sclerosis. (13th August 2019) - Laplaud, David-Axel; Casey, Romain; Barbin, Laetitia; Debouverie, Marc; De Sèze, Jérôme; Brassat, David; Wiertlewski, Sandrine; Brochet, Bruno; Pelletier, Jean; Vermersch, Patrick; Edan, Gilles; Lebrun-Frenay, Christine; et al.
Abstract : Objective: In this study, we compared the effectiveness of teriflunomide (TRF) and dimethyl fumarate (DMF) on both clinical and MRI outcomes in patients followed prospectively in the Observatoire Français de la Sclérose en Plaques. Methods: A total of 1, 770 patients with relapsing-remitting multiple sclerosis (RRMS) (713 on TRF and 1, 057 on DMF) with an available baseline brain MRI were included in intention to treat. The 1- and 2-year postinitiation outcomes were relapses, increase of T2 lesions, increase in Expanded Disability Status Scale score, and reason for treatment discontinuation. Propensity scores (inverse probability weighting) and logistic regressions were estimated. Results: The confounder-adjusted proportions of patients were similar in TRF- compared to DMF-treated patients for relapses and disability progression after 1 and 2 years. However, the adjusted proportion of patients with at least one new T2 lesion after 2 years was lower in DMF compared to TRF (60.8% vs 72.2%, odds ratio [OR] 0.60, p < 0.001). Analyses of reasons for treatment withdrawal showed that lack of effectiveness was reported for 8.5% of DMF-treated patients vs 14.5% of TRF-treated patients (OR 0.54, p < 0.001), while adverse events accounted for 16% of TRF-treated patients and 21% of DMF-treated patients after 2 years (OR 1.39, p < 0.001). Conclusions: After 2 years of treatment, we found similar effectiveness of DMF and TRF in terms of clinical outcomes, but with better MRI-based outcomes for DMF-treated patients, resulting in a lower rate of treatment discontinuation due to lack of effectiveness. Classification of evidence: This study provides Class III evidence that for patients with RRMS, TRF and DMF have similar clinical effectiveness after 2 years of treatment.